Corrosion and Wear Properties of Building Direction Dependent as-Built AlSi10Mg Aluminium Alloy Printed by Selective Laser Melting - Tarakçı, Gürkan; Kısasöz, Burçin Özbay; Özer, Gökhan; Kısasöz, Alptekin (Elsevier, 2025)
In this study, poly(methyl methacrylate) (PMMA) nanofiber scaffolds reinforced with synthesized nano-hydroxyapatite (n-HA) were fabricated through electrospinning to enhance their potential for applications in bone tissue engineering. Sodium tripolyphosphate (STTP) was utilized as a surfactant to achieve a uniform distribution of particles and improve the structural integrity of the scaffolds. PMMA solutions were prepared at concentrations of the addition of STTP effectively stabilized n-HA dispersion, leading to enhanced fiber morphology, as confirmed by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and transmission electron microscopy (TEM). The PMMA_10_HA_S nanofibers demonstrated a homogeneous fiber distribution with an average diameter of 345.40 ± 53.55 nm and a calcium content of 7.1%. Mechanical testing revealed that adding STTP enhanced the mechanical properties, with the n-HA-reinforced 10 wt.% PMMA nanofibers achieving a maximum tensile stress of 4.16 ± 2.13 MPa and an elongation of 7.1 ± 1.95%. Furthermore, cell cytotoxicity assays of different concentrations (25, 50, 75, and 100 mg/mL) using L929 fibroblast cells demonstrated no cytotoxic effect of PMMA_10_HA_S nanofibers. These findings, reinforced by STTP and n-HA, highlight the potential of PMMA_10_HA_S nanofiber scaffolds as promising candidates for bone tissue applications
Keywords: Additive Manufacturing; Aluminium; Wear; Corrosion Behaviour